2014
DOI: 10.1371/journal.pone.0099856
|View full text |Cite
|
Sign up to set email alerts
|

Cord Blood 25(OH)-Vitamin D Deficiency and Childhood Asthma, Allergy and Eczema: The COPSAC2000 Birth Cohort Study

Abstract: BackgroundEpidemiological studies have suggested an association between maternal vitamin D dietary intake during pregnancy and risk of asthma and allergy in the offspring. However, prospective clinical studies on vitamin D measured in cord blood and development of clinical end-points are sparse.ObjectiveTo investigate the interdependence of cord blood 25-hydroxyvitamin D (25(OH)-Vitamin D) level and investigator-diagnosed asthma- and allergy-related conditions during preschool-age.MethodsCord blood 25(OH)-Vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
95
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 39 publications
6
95
1
2
Order By: Relevance
“…33,47,48 The 9 studies with nonsignificant results used a variety of 25(OH)D thresholds. 29,30,32,[40][41][42][43][44]46 None of the 6 studies looking at the association between 25(OH)D and allergic rhinitis reported significant associations. 29,30,41,43,44,48 One study mentioned collecting data but did not report on the outcome.…”
Section: Allergic Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…33,47,48 The 9 studies with nonsignificant results used a variety of 25(OH)D thresholds. 29,30,32,[40][41][42][43][44]46 None of the 6 studies looking at the association between 25(OH)D and allergic rhinitis reported significant associations. 29,30,41,43,44,48 One study mentioned collecting data but did not report on the outcome.…”
Section: Allergic Diseasementioning
confidence: 99%
“…Most cohorts excluded women with prior serious medical issues, problems during pregnancy, congenital defects, or premature delivery, except as follows: 2 studies (same cohort) included women with prior HIV infection, 26,27 4 studies preferentially recruited parents with a history of allergic disease, [28][29][30][31] and 3 studies included all expectant mothers who presented to the study sites, regardless of health status.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors also conjectured that maternal vitamin D deficiency could explain the association. Vitamin D is involved in development of the fetal immune system and lungs, and low vitamin D has been associated with higher risk of infections in pregnancy [26] and offspring asthma [27]. Vitamin D supplementation has been shown to reduce risk of infections and, nonsignificantly, antibiotic use [28].…”
mentioning
confidence: 99%
“…Cord blood vitamin D level and multi-trigger wheezing, wheezing and risk of troublesome lung symptoms development have been reported to be reversely correlated in three different studies [35,36]. However, recent two different birth cohort studies showed that cord blood vitamin D concentrations were unrelated to atopy and wheeze [37].…”
Section: Natal Umblical Cord Vitamin D Level and Wheezing Developmentmentioning
confidence: 99%